2018
DOI: 10.5603/ait.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline-hydroxyethyl starch solution attenuates fluid accumulation in cardiac surgery patients: a randomized controlled double-blind trial

Abstract: Our study shows that 250 mL of HS-HES solution can reduce perioperative fluid accumulation to some degree in patients undergoing CABG surgery with CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In their respective studies, Mortazavi et al and Grande et al referred to the potential occurrence of the rebound phenomenon when pointing out weaknesses and side effects of osmotherapeutics [32,33]. This results from the transiency of cell shrinkage, volume reduction and hemodynamic effects gained from the infusion of osmotic agents [34]. White et al showed the association between the repeated dosage of osmoactive agents and an increase in ICP and edema up to the values nearing or even exceeding, the initial pre-treatment measurements [35].…”
Section: Discussionmentioning
confidence: 99%
“…In their respective studies, Mortazavi et al and Grande et al referred to the potential occurrence of the rebound phenomenon when pointing out weaknesses and side effects of osmotherapeutics [32,33]. This results from the transiency of cell shrinkage, volume reduction and hemodynamic effects gained from the infusion of osmotic agents [34]. White et al showed the association between the repeated dosage of osmoactive agents and an increase in ICP and edema up to the values nearing or even exceeding, the initial pre-treatment measurements [35].…”
Section: Discussionmentioning
confidence: 99%